PERENCANAAN SARANA DAN PRASARANA SMK NEGERI 2 BINJAI - Sam, Rizka Ramadani (IKAMAS: Manajemen Pendidikan Islam, 2021)
In order to improve the quality of national education, the government has made various efforts as also contained in Law Number 20 of 2003 concerning the National Education System which includes the basis and objectives of providing education including compulsory education, guaranteeing the quality of education and the role of the community in the national education system. The purpose of writing this article is to find out the Facilities and Infrastructure Planning Process at SMK N 2 Binjai. This article uses a descriptive qualitative research approach method. This descriptive qualitative research approach method is carried out by describing and disclosing the management of school facilities and infrastructure at SMK N 2 Binjai. Researchers will try to explain specifically, in detail and in detail about such as the planning process of school facilities and infrastructure at SMK N 2 Binjai in accordance with the facts on the ground. The subject of his research was the vice principal of the facilities and infrastructure section at SMK N 2 Binjai. The results showed that the planning of facilities and infrastructure at SMK N 2 Binjai is the initial stage in the management of facilities and infrastructure in the school, in the planning there is a whole process of carefully estimating the design of facility needs needed by students, teachers and all staff at SMK N 2 Binjai.